GERMPLASM EVALUATION OF CORIANDER (CORIANDRUM SATIVUM L.) ON YIELD AND YIELD RELATED TRAITS - ALI , A; KHAN , MA; NADEEM , K; TAHIR , A; TAHIR , Z; CHAUDHARY , M; SULTANA , R; REHMAN , M; ZULQAR , M; GHIAS , M (Biological and Clinical Sciences Research Journal, 2024)
The Germplasm of coriander comprising of five genotypes including DILPAZEER commercial variety were evaluated at Vegetable Research Institute, Faisalabad. The genotypes under evaluation were subjected to analysis of variance and showed significant variance in all of the studied morphological features. The most significant variance was found in yield and yield related traits. DILPAZEER (CHECK) and GGAS-COR-67 emerged as top performers due to their high leaf yield, favorable plant height, and reasonable cutting times. ECO 1212 A also showed promising results due to its early cutting times and decent yield. HSV-553, while taking the longest time to mature, showed the lowest yield, making it less favorable for high-output production. DILPAZEER (CHECK) excels in plant height, number of leaves, and leaf yield, remained ideal candidate for high-yield production.